2020
DOI: 10.5194/hess-24-1367-2020
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the 2015 Salgar flash flood using radar retrievals and a conceptual modeling framework in an ungauged basin

Abstract: Abstract. On 18 May 2015, a severe rainfall event triggered a flash flood in the municipality of Salgar, located in the northwestern Colombian Andes. This work aims to reconstruct the main hydrological features of the flash flood to better understand the processes modulating the occurrence of the event. Radar quantitative precipitation estimates (QPEs), satellite information, and post-event field visits are used to reconstruct the Salgar flash flood, in an ungauged basin, addressing the relationship among rain… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 77 publications
1
3
0
1
Order By: Relevance
“…According to our results, convective systems occur more often in areas with high topographical gradients, where the aspect is opposite to the wind direction. This result coincides with other studies performed in the region around rainfall and topography [55,59]. Moreover, similar results linking topography and convective rainfall have been reported in other regions [60][61][62][63][64].…”
Section: Discussionsupporting
confidence: 92%
“…According to our results, convective systems occur more often in areas with high topographical gradients, where the aspect is opposite to the wind direction. This result coincides with other studies performed in the region around rainfall and topography [55,59]. Moreover, similar results linking topography and convective rainfall have been reported in other regions [60][61][62][63][64].…”
Section: Discussionsupporting
confidence: 92%
“…The research was mainly focused on the following three major regions: Continental Europe [22][23][24][25][26] with about 40% of articles, Asia with 28% [27][28][29][30][31], and North America with 20% [32][33][34][35][36]. South America (5%) [37][38][39][40][41] and Africa (4%) [42][43][44][45][46] showed less research interest (Figure 2). Following a detailed analysis of each region, we found that the most researched areas were: the United States, representing 13.19% of the total articles analyzed and 71.72% of the articles located in North America [47][48][49]; the United Kingdom, with 90 articles representing 17.92% of the articles in Europe and 6.78% of the total papers [50][51][52]; Italy and Spain, accounting for 5.27% of the entire articles and 13.94% of the scientific papers published in Europe, respectively [53][54][55]; and China, accounting for 5.27% of the total articles and 20.11% of the articles in Asia [56][57][58].…”
Section: Spatial Distribution Of Researchmentioning
confidence: 99%
“…De acordo com Vanelli et al, (2020), no Brasil, ainda não existem normativas, como na UE, que incentivam a investigação de eventos passados para apoiar a gestão de risco e de desastres. Esse tipo de estudo, denominado reconstrução por Balasch et al (2010), Barriendos et al (2014) e Vanelli et al (2020, entre outros, refere-se a representar um certo evento ocorrido visando determinar os fatores associados aos processos físicos e avaliar as interações entre as variáveis possibilitando uma melhor compreensão dos mecanismos envolvidos (Fortunato et al 2017;Velásquez et al, 2020). Entretanto, outros termos já foram utilizados com o mesmo propósito: retromodelagem (Remo & Pinter, 2007;Balasch et al, 2011) e reconstituição (Ribeiro Neto et al, 2015).…”
Section: Uso Integrado De Dados Sistemáticos E Não Sistemáticos Na Hi...unclassified